SISTEM ISNĀD HADĪTS DAN AWAL MULA PENGGUNAANNYA DALAM TRADISI PERIWAYATAN PUISI ARAB JAHILIYAH - Ahmad, Lalu Turjiman (ALQALAM, 2011)
It is ordinary that riwāyah (oral transmission) has been the main media in transmitting knowledge. Indeed, for the Arabs, the transmission system was used not only in transmitting hadits, but also in transmitting the history. In terms of the transmission of traditions, the transmitters were very strict in applying the rules of transmission. Hence, such an isnād system has a very important value in the history. Muslims in the past gave much attention to such an isnād system.The transmissions of poetry had been emerged before the transmissions did. Every poetry has the transmitters. They keep and guarantee the continuity of the poetry transmission. The relation between the poetry transmitters and their poetries is not different from that of the transmitters of hadits and their hadits. Key words: hadits, isnād, Jahiliyah poetry, oral transmission.